High‐Speed Stereo Digital Image Correlation: Application to Biaxial Fatigue. (20th February 2014) - Busca, D.; Fazzini, M.; Lorrain, B.; Mistou, S.; Karama, M.; Pastor, M. L.
ABSTRACT To study the behaviour of a carbon‐fibre reinforced‐plastic laminate under a biaxial stress state, a new type of cruciform specimen has been developed. This specimen is loaded biaxially under static and cyclic fatigue conditions. The experiments are monitored simultaneously using digital image correlation with two high‐speed cameras and infrared thermography. A comparison between the measurements and a finite element model is used to validate the design of the sample.